(3GdJfhjQ aj ESbGW GdJOHjQs - (3CMeO Hf eMeO Hf YHO GdcQje Hf YWGA Gddg GdScfOQj, GHf YWGA Gddg , JGL GdOjf CHh GdaVd,J (B709 (3g` s
(3ChdgG (B:s
(3CeG HYO GYde jG CNj LYdc Gddg ef Cgd MHg hCJMac HhLhO bQHg s
(3BNQgG (B:s
(3eJHYjf dQShdc hGQKjf Yfg hBNPjf efg Je cJGH GdJfhjQ HMeO Gddg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B121s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B502s
Keywords: (3GdJUha hGdBOGH GdTQYjIs